Factors Influencing in Selection of MBA Programs: An Empirical Investigation in Malaysian Higher Learning’s Institutions - Sarwar, Abdullah Al-Mamun; Haque, A. K. M. Ahasanul (2012)
Different higher learning institutions in Malaysia are offering various courses for the students. But selection of the institute is varied considering the different influencing factors. In this study, the different factors influencing the MBA students in selection of their higher learning institutions in Malaysia will be discussed and analyzed by various statistical techniques. It has been observed from the outcome of the literature review that, university teaching quality is the most important factor that influences a student in selection of his higher learning institution. Different questions will be asked to determine the most influencing term under university teaching quality. On perception, a proper policy may go a long way to increase the quality of teaching with the improvement of other related facilities which will help the university in attracting new students.